2014
DOI: 10.1111/ans.12814
|View full text |Cite
|
Sign up to set email alerts
|

Extramammary Paget's disease of the perianal region: a 20‐year experience

Abstract: PPD is a management challenge. Association with synchronous and metachronous carcinomas may not be as strong as initially thought. Surgery is the mainstay treatment with the need to balance between minimizing disease recurrence and functional sequelae from excessive tissue loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Perianal involvement comprises 20% of EMPD cases in both genders and has the highest incidence of related underlying malignancy . Reported rates of underlying malignancy range from 33% to 86% and are typically rectal or tubo‐ovarian cancers …”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perianal involvement comprises 20% of EMPD cases in both genders and has the highest incidence of related underlying malignancy . Reported rates of underlying malignancy range from 33% to 86% and are typically rectal or tubo‐ovarian cancers …”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Depending on the anatomic location involved, certain underlying malignancies may appear more frequently. For example, perianal lesions are more commonly associated with anal or colorectal carcinomas . Accordingly, depending on the gender of the patient, appropriate studies to be considered include mammography, pap smear, pelvic ultrasonography, cystoscopy, colonoscopy, and computed tomography of the abdomen and pelvis …”
Section: Screening For Malignancymentioning
confidence: 99%
“…This is because PPD tends to present a discontinuous spread of pagetoid cells in the epidermis beyond the clinically apparent margin, and the entire lesion is consequently very difficult to remove with no residual cells remaining [19]. As a consequence, according to the literature, after surgery, patients with noninvasive lesions must undergo periodic proctoscopies and digital examinations, while the follow-up of patients with invasive diseases should include CT scan for lung and liver evaluation as well as the examination of inguinal lymph nodes [20]. There are no randomized trials in the literature to demonstrate the effectiveness of adjuvant therapy for this type of disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…There is still no consensus regarding the optimal resection margin within the anal canal. Previous case reports suggested that resection of the anal canal mucosa up to 1 cm above the dentate line is important to ensure inclusion of the entire anal squamous epithelium 4 15 . However, the resection margin within the anal canal should be carefully determined as excessive resection may easily impair the postoperative anorectal function.…”
Section: Discussionmentioning
confidence: 99%